Foodomics in wheat flour reveals phenolic profile of different genotypes and technological qualities. (January 2022) - Barros Santos, Millena Cristina; Ribeiro da Silva Lima, Luciana; Thomaz dos Santos D'Almeida, Carolina; Mayrinck Victorio, Verônica Cristina; Cameron, Luiz Claudio; Bourlieu-Lacanal, Claire; Simões Larraz Ferreira, Mariana
Abstract: Phenolic compounds (PC) strongly contribute to the beneficial health effects of wheat, but their interactions can affect the quality of end-use wheat products. Free and bound PC were comprehensively characterized in 14 wheat flours ( Triticum aestivum ) from different Brazilian genotypes and technological qualities by using a metabolomics approach (UPLC-ESI-QTOF-MS E ) combined with classical characterizations: colorimetry, ash, protein, starch and total phenolic content (TPC). Globally, 43 PC were identified: 33 (bound, 28 (free) and 15 in all flours, regardless of extract. Ferulic acid isomers were the most abundant PC, representing 25–50% of ion abundance depending on genotype. Campeiro, Sossego and Topázio genotypes showed a distinguished profile, with the highest total relative abundance of PC. TPC was significantly higher in flours with higher gluten strength (66.5–58.0 mg GAE/100 g flour). The ratio free-to-bound of PC averaged 1.15 between the flours of different technological qualities. Although PCA highlighted specific PC related to technological qualities, the genotype effect was very pronounced. This study correlates the phenolic profile and technological quality of wheat flours and provides the most recent data on the secondary metabolites profile, especially PC in refined flour, attesting to its significant nutritional importance due to its large consumption in refined forms. Graphical abstract: Image 1 Highlights: First study to correlate phenolic profile and technological quality in Brazilian wheat flours. Metabolomics reveals the phenolic profile in different Brazilian genotypes in wheat flours. Phenolic compounds persist after the milling process in refined wheat flours. Twenty phenolic compounds were detected in all genotypes studied. Multivariate analysis highlighted discriminating compounds among the technological qualities.